COMPARISON OF ECDSA DAN EDDSA ALGORITHMS IN BLOCKCHAIN-BASED HEALTH RECORDS SECURITY - Nicholas Alexander; Bayu Angga Wijaya; Rico Wijaya Dewantoro; Monalisa Monalisa (JIKO (Jurnal Informatika dan Komputer), 2025)
The development of blockchain technology presents significant opportunities for the management of Electronic Health Records (EHR), owing to its decentralized, transparent, and tamper-resistant characteristics. However, security challenges remain, particularly regarding the use of the Elliptic Curve Digital Signature Algorithm (ECDSA), which, despite being compact and secure, has limitations in efficiency and potential vulnerabilities related to random nonce usage. This study aims to compare the effectiveness, efficiency, and security of ECDSA with the Edwards-curve Digital Signature Algorithm (EdDSA) in safeguarding the integrity and confidentiality of blockchain-based EHR systems. The research methodology involved simulations and evaluations of digital signature algorithms using an EHR dataset from Kaggle, focusing on performance testing, data validation, and the implementation of the Proof-of-Work (PoW) consensus mechanism. The results indicate that EdDSA outperforms ECDSA in terms of both speed and security. EdDSA achieved a signing time of 0.000180 seconds and a verification time of 0.000200 seconds, compared to ECDSA's 0.000962 seconds and 0.003204 seconds, respectively. While both algorithms successfully validated the data, neither was able to detect data alterations. From a blockchain perspective, PoW demonstrated high computational resistance, as evidenced by increased mining times—from 1,504 seconds for 4,000 blocks (difficulty target = 5) to 7,702 seconds for 20,000 blocks (difficulty target = 5)—thereby enhancing system integrity. Overall, EdDSA is considered more suitable for modern blockchain-based EHR implementations, although further research is needed to develop mechanisms for detecting data alteration.